Pengaruh Pengungkapan CSR Terhadap Kualitas Audit - Ade Elza Surachman (Universitas Muhammadiyah Metro, 2020)
This research aims to test and empirically prove the effect of corporate social responsibility disclosure on the audit quality. Audit quality measurement in this research uses natural logarithm to audit fees while CSR reporting is measured using a content analysis approach. The population of this research is the sub-sector transportation of companies listed in the Indonesia Stock Exchange in 2010 until 2017. The annual report contains disclosure of corporate social responsibility activities of 4 companies that using a purposive sampling technique. Methods of data analysis using descriptive statistical analysis and simple linear regression. These results indicate that corporate social responsibility disclosures have a significant effect simultaneously and partially on the audit quality